Studies on hot corrosion behaviour of A-TIG welded AISI 316 weldments. (2018) - Rebin Sanford, B.; Venkatesh, K.M.; Arivarasu, M.; Manikandan, M.; Hari, K.T.; Mithun, K.G.; Surya, P.R.; Arivazhagan, N.
Abstract: Hot corrosion of weldments is a major problem in various industrial applications such as gas turbines, diesel engines and furnaces etc. The work carried out consists ofsimilar weldments of 8 mm thick 316L made by activated TIG welded samples when exposed to high temperature molten salts of V2 O5 + 60%wt NaCl at 650°C under cyclic conditions. The kinetics of corrosion of weldment was determined from the weight change of the samples calculated during the experiments.After the process of hot corrosion the material properties of the products were characterized by SEM/EDAX and XRD techniques.